A study of the deltaic coast morphometry of river Pinios in relation to its hydro- & sediment dynamics - Foutrakis, P.; Poulos, S.; Maroukian, H.; Livaditis, G. (Bulletin of the Geological Society of Greece, 2007)
This paper refers to the study of the morphodynamic processes, on a seasonal basis, in the river delta of Pinios (Greece) with the application of the discharge effectiveness index (Ef) -which associates the water discharge (D) with the wave power (PJ- and the estimation of the potential longshore sediment transport (Ql). The delta is characterised according to the classification proposed by Galloway (1975) and revised by Briggs et al (1997), as wave/fluvial dominated type of delta, having a cuspate shape like the deltas of San Francisco and Rhone. Wave processes are dominant during summer-autumn period (low values ofEf) and river processes are important in winter and spring (high values ofEf). The total potential longshore sediment transport is northwards and more intensive in the region to the south of its current mouth.